(untitled) (Research, Society and Development, 2022)
Seen the constant expansion of wind energy in the global energy scenario, it is necessary to present methods capable of reproducing the electromechanical effects of this source, in order to improve knowledge and technological advances. The aim of this work was to implement and evaluate the performance of the laboratory methodology for reproduction of wind turbines, using electrical machines controlled via software. For that, a platform was developed in LabVIEW for modeling and controlling the wind system, employing a direct current motor to reproduce the power extracted by the turbine, being coupled to the axis of a synchronous generator feeding a energy consuming load. The system performance study was based on the simulation of three cases, seeking to analyze parameters of constant operation, incidence of wind turbulence and behavior of the turbine control system. The results archived were gratifying by the didactic model on a reduced scale, which made it possible to verify the electromechanical effects arising from the imposed conditions. It was found that the operation of the turbine changes significantly for small wind alterations, influencing the extraction of mechanical power and the voltages generated by the system.